The influence of Thailand's 2003 'war on drugs' policy on self-reported drug use among injection drug users in Chiang Mai, Thailand - Tassanai Vongchak (2018)
In February 2003, the Thai Government enacted a 'war on drugs' to reduce supply and demand for illicit drugs. This study aimed to examine the impact of this policy on injection drug users (IDUs) drug utilisation patterns and to explore IDU attitudes toward and experiences with the policy in Chiang Mai province. In April 2003, 263 IDU who participated in a study in the preceding year were followed up and 165 IDUs (63%) were available and consented to participate in a cross-sectional survey. Of these 85% had ceased injecting and 70% had done so since the implementation of the policy, with a higher percentage of rural compared to urban IDUs ceasing injection (78% versus 55%, p < 0.001). One-third of those who had ceased drug injection reported smoking opium or methamphetamine, with a lower percentage of urban compared to rural dwellers (24% versus 36%, p < 0.01). Paradoxically, 88% of participants reported that government policy was "good," ostensibly because it might reduce the temptation to use drugs among the non-initiated by reducing the supply. The majority of study participants reported ceasing injection, often transitioning to other substance use. Differences in drug utilisation patterns were found between urban and rural dwellers. The fear produced by the policy probably led to an underreporting of injection practices and could lead to increased risky syringe behaviours. Continued research is needed to monitor the effects of the policy on patterns of drug use, routes of administration, and HIV risk behaviours. © 2004 Elsevier B.V. All rights reserved.